2014
DOI: 10.1039/c4ta01828a
|View full text |Cite
|
Sign up to set email alerts
|

High performance Pt-free cathode catalysts for polymer electrolyte membrane fuel cells prepared from widely available chemicals

Abstract: A high performance Pt-free cathode catalyst for polymer electrolyte fuel cells has been synthesized by the multi-step pyrolysis of polyimide fine particles with a diameter of about 100 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
(30 reference statements)
0
59
0
1
Order By: Relevance
“…Then, in a second step and for all selected catalysts, the time evolution of their fuel cell performance can be compared, either in H 2 /O 2 and/or in H 2 /Air depending upon which experimental conditions are reported for the durability tests in the literature. When the initial maximum performance of the cell is set at !0.5 W cm À2 in H 2 /O 2 , the long list of non-PGM catalysts enumerated above is reduced to merely five catalysts which are delivering a maximum initial power of 0.55 [27], 0.60 [11], 0.62 [22], 0.73 [21], and 0.90 Wcm À2 [5], respectively. To this short list of catalysts, one may also add the catalyst, whose maximum initial performance (0.33 W cm À2 [34]) was the only one reported in H 2 /Air for a maximum initial power set at !0.25 W cm À2 (half of !0.5 W cm À2 set for the initial maximum performance measured in H 2 /O 2 fuel cell).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in a second step and for all selected catalysts, the time evolution of their fuel cell performance can be compared, either in H 2 /O 2 and/or in H 2 /Air depending upon which experimental conditions are reported for the durability tests in the literature. When the initial maximum performance of the cell is set at !0.5 W cm À2 in H 2 /O 2 , the long list of non-PGM catalysts enumerated above is reduced to merely five catalysts which are delivering a maximum initial power of 0.55 [27], 0.60 [11], 0.62 [22], 0.73 [21], and 0.90 Wcm À2 [5], respectively. To this short list of catalysts, one may also add the catalyst, whose maximum initial performance (0.33 W cm À2 [34]) was the only one reported in H 2 /Air for a maximum initial power set at !0.25 W cm À2 (half of !0.5 W cm À2 set for the initial maximum performance measured in H 2 /O 2 fuel cell).…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts have indeed shown to be highly active and performing at the beginning of their lives, but their durability still needs to be greatly improved in order to become serious contenders to Pt [4,5] The literature reporting the durability of pyrolyzed Fe-or/and Co/N/C catalysts at the cathode of PEM fuel cells is rather scarce but increased in the recent years. A minority of durability experiments were performed at constant current in pure H 2 /O 2 [6][7][8][9], or in H 2 /Air [10,11], while the majority of stability fuel cell tests were obtained at constant potential either: (i) in pure H 2 /O 2 at 0.4 V [12][13][14][15][16][17], or at 0.5 V [4,5,[18][19][20][21][22], or (ii) in H 2 /Air at 0.4 V [4,[23][24][25][26][27][28][29][30], or at 0.5 V [5,18,[31][32][33], or at 0.6 V [30,34,35]. All these stability tests were performed for various durations at different fuel cell temperatures (mostly 80 C), gas humidification, feeding rates and backpressures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the groups of Dodelet and Nabae reported that iron-and/or cobalt-complex-based catalysts, such as Fe-N-C 12 and carbon-based catalysts 13 have high single-cell performance comparable to that of Pt/C cathodes. Recently, Cheon et al also reported that Fe-and Co-doped ordered mesoporous porphyrinic carbons have higher ORR activity than Pt/C in 0.1 M HClO 4 solution.…”
mentioning
confidence: 99%
“…To successfully commercialize PEFCs, lowcost non-platinum cathode catalysts with high stability must be developed. Iron-and/or cobalt-complex-based catalysts such as Fe-N-C [1], carbon-based catalysts [2], and chalcogenides [3] have been investigated as non-platinum cathode catalysts under cathode conditions for PEFCs. Recently, Cheon et al reported that the oxygen reduction reaction (ORR) activities of Fe-and Co-doped ordered mesoporous porphyrinic carbons were greater than that of platinum [4].…”
Section: Introductionmentioning
confidence: 99%